Quebec’s Institutional Reconfiguration and the Reengineering Process: Lessons from Ontario - Gagnon, Alain-G; de Champlain, Olivier (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2006)
The sustained interest in the potential of the public-private partnership formula (PPP) to take on the challenges relating to public finance crises and a gap in infrastructure faced by several countries is fuelled by a discourse on efficiency, and by the novelty and uniqueness of the way every political entity (state, province) is managing its PPPs. The discourse surrounding PPPs, built around themes like cooperation, corporate accountability and service improvement, is replacing the language of competition that was commonplace during the late 1970s and early 1980s. To some, these discourses represent the latest chapter in “the privatization of government services”, whereas others criticize the confusion and rhetoric built around a concept in the process “of becoming just another public policy reform fad.” Inspired by a text written by Neil Bradford, we explore the outcomes of two economic innovation strategies that occurred respectively under the reign of Bob Rae’s NDP government (1990-1995) and Mike Harris’ Conservatives (1995-2002) in Ontario. Bradford makes the point that the Conservatives narrow and market-based partnership approach succeeded where the NDP’s broad partnership approach failed. This was in part due to an inadequate institutional configuration. Based on this observation, the case of Quebec will be assessed in order to determine whether there is a better institutional fit between the reengineering process being considered and the Quebec government’s potential for innovation and its state capacity.